Black and white women: a socio-historical study of domestic workers and their employers in the Eastern Cape - Cock, Jacklyn (Rhodes University, Faculty of Humanities, Department of Sociology, 1981)
Domestic service constitutes one of the largest sources of employment for black women in South Africa. Yet it is a largely unstudied occupation. There has been no previous investigation of domestic workers in the Eastern Cape, and to date only two comprehensive studies of domestic workers in other areas of South Africa. This neglect is significant, for such inquiry involves questioning the accepted pattern of inequalities on which the entire social order is based.
Keywords: Household employees -- South Africa; Working class -- South Africa; Women, Black -- Employment -- South Africa; South Africa -- Race relations